Data linkage to national Australian health insurance data to investigate exposure to environmental hazards: the example of residential asbestos. (2018) - Anderson, Phil; Korda, Rosemary; Law, Hsei Di; Kirk, Martyn; Guiver, Tenniel
No abstract available